Mathematical modeling of the gasdynamic charcteristics of the heat-transfer medium jet in a process of the thermal reaming of the borehole - Voloshyn, O.I.; Potapchuk, I.Yu.; Zhevzhyk, O.V.; Yemelianenko, V.I.; Teplyi, V.P.; Kholyavchenko, L.T.; Shniakin, S.V. (Геотехнічна механіка, 2017)
Purpose of the work is to develop a mathematical model for calculation of gasdynamic characteristics (pressure, density, speed) of the heat-transfer medium at its movement along the surface of the borehole in the process of its thermal reaming. For this purpose, technique and algorithm were developed for calculation of gas-dynamic characteristics of the free and semibounded jet of the heat-transfer medium at its movement along the surface of the borehole.